2014
DOI: 10.1111/bjd.12935
|View full text |Cite
|
Sign up to set email alerts
|

The current and future role of general practitioners in skin cancer care: an assessment of 268 general practitioners

Abstract: Most GPs are willing to extend their role in SC care; however, more training is requested and the usage of guidelines should be encouraged. Those willing to extend their role should focus on improving their clinical diagnosis of skin tumours, treatment of low-risk skin (pre)malignancies, including field-directed treatment of AK and noninvasive treatment of BCC, and on prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…This may have led to selection bias in their preference for a dermatologist as a healthcare provider. As the role of GPs in BCC care is currently expanding, future focus groups may also be organized in a primary‐care setting. By organizing six focus groups in different medical specialist settings, we were able to create a representative sample of patients with KC treated by dermatologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have led to selection bias in their preference for a dermatologist as a healthcare provider. As the role of GPs in BCC care is currently expanding, future focus groups may also be organized in a primary‐care setting. By organizing six focus groups in different medical specialist settings, we were able to create a representative sample of patients with KC treated by dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of a subsequent BCC is high (29% in 5 years), evidence is lacking that regular follow‐up visits translate into improved patient outcomes . In addition, another trend aimed to reduce costs has been care substitution, which aims to shift skin cancer care from medical specialists towards general practitioners (GPs), or nurse practitioners (NPs) and physician assistants (PAs) specialized in dermatology . It is of paramount importance that these GPs, NPs and PAs have had sufficient dermatological training.…”
mentioning
confidence: 99%
“…Although 54% of PCPs suggest having sufficient skills for diagnosing skin cancer, 37 greater than 50% are requesting further knowledge to aid in the process. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In countries such as Australia, where skin cancer poses a large burden on the healthcare systems, trained GPs with a special interest in skin cancer are functioning as specialized primary care physicians to detect and treat skin cancer. A Dutch study showed that the majority of GPs questioned were willing to extend their role in skin cancer care, including surgical excision of low‐risk BCCs, but that they requested additional skin cancer training …”
Section: Implications For Health Policiesmentioning
confidence: 99%
“…A Dutch study showed that the majority of GPs questioned were willing to extend their role in skin cancer care, including surgical excision of low-risk BCCs, but that they requested additional skin cancer training. 186 Choosing the most cost-effective treatment for BCC wisely becomes increasingly important. 187 The positioning and appropriate use of MMS in the management strategy of BCC is crucial, because it drives the increment in costs related to BCC care.…”
Section: Treatment-related Impactmentioning
confidence: 99%